Effect of Frequency of Administration of Kappa-Carrageenan on Immune Response and Survival of Vibrio parahaemolyticus Infected Vannamei Shrimp (Litopenaeus vannamei) - Febrianti, Baiq Yunita; Azhar, Fariq; Mukhlis, Alis (Jurnal Biologi Tropis, 2025)
Whiteleg shrimp (Litopenaeus vannamei) cultivation activities are often exposed to disease-causing pathogens, one of which is a bacterial disease from the genus Vibrio sp. One of the triggers is the accumulation of organic matter, leftover feed and feces in the waters which causes whiteleg shrimp to be toxic to NH3. Kappa carrageenan is a polysaccharide compound derived from red seaweed that has the potential as a natural immunostimulant. The study aimed to determine the effect of administering kappa carrageenan at different frequencies on the defense system of shrimp infected with Vibrio parahaemolyticus bacteria. The study used RAL, with 5 treatments and 3 replications. The highest Survival Rate (SR) value was found in P5 at 80% and the lowest in P3 at 22%. The highest RPS value was found in P5 at 94.82% which was given carrageenan once a week and the lowest in P3 at 82.18% which was given carrageenan every day. The highest THC amount was observed in P5 at 14.9 x 106 cells/ml and the lowest was in P1 at 5.01 x 106 cells/ml. The highest AF value was in the positive control treatment P1 66.6% and the lowest P2 negative control 44.2%. The highest TBC value was P1 1.24 CFU/mL and the lowest P5 0.29 CFU/mL. The highest TVC observation was P5 1.42 CFU/mL and the lowest was P1 0.18 CFU/mL. In conclusion, the administration of k-carrageenan 20 g/kg once every 7 days provided a better immune response and protection against shrimp infected with Vibrio parahaemolyticus bacteria.